2008
DOI: 10.17660/actahortic.2008.797.48
|View full text |Cite
|
Sign up to set email alerts
|

Energy Saving and Solar Electricity in Fan-Ventilated Greenhouses

Abstract: Greenhouse cultivation is an energy intensive process therefore it is worthwhile to introduce energy saving measures and alternative energy sources. Here we show that there is scope for energy saving in fan ventilated greenhouses. Measurements of electricity usage as a function of fan speed have been performed for two models of 1.25m diameter greenhouse fans and compared to theoretical values. Reducing the speed can cut the energy usage per volume of air moved by more than 70%. To minimize the capital cost of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The cost data for the GH and PV-powered cooling system were taken from current prices of off-the-shelf components used. In Davies et al [21], it was shown that a GH ventilation system can be constructed with energy usage as low as 20 J per m 3 of air moved, and this has been taken as the basis for the sizing and costing of the PV generators in the system. The Table 5 Parameters used in the model of the cooled GH.…”
Section: Choice Of Datamentioning
confidence: 99%
“…The cost data for the GH and PV-powered cooling system were taken from current prices of off-the-shelf components used. In Davies et al [21], it was shown that a GH ventilation system can be constructed with energy usage as low as 20 J per m 3 of air moved, and this has been taken as the basis for the sizing and costing of the PV generators in the system. The Table 5 Parameters used in the model of the cooled GH.…”
Section: Choice Of Datamentioning
confidence: 99%
“…The same method of seawater-evaporative cooling was subsequently applied in the UAE and in Oman through collaborations between Seawater Greenhouse Ltd and Sultan Qaboos University [9]. Seawater Greenhouse Ltd implemented a further project in Australia, which remains in operation under the name of Sundrop Farms (www.sundropfarms.com), also incorporating a solar-PV fan system to reduce fossil fuel consumption [10]. More recently, the Sahara Forest Project implemented a greenhouse in Qatar that uses seawater evaporative cooling (http://saharaforestproject.com).…”
Section: Global Contextmentioning
confidence: 99%
“…The another approach is a planar optical matrix embedded with a luminescent material, based on the idea of light-pipe trapping molecular or ionic photoluminescence. [18][19][20][21][22][23] Incident photons absorbed by the luminescent centers inside the optical matrix are subsequently remitted and trapped by total internal reflection. This trapped light escapes the edges of the waveguide and is converted into electricity by appropriate photovoltaic solar cells.…”
Section: Introductionmentioning
confidence: 99%